2021
DOI: 10.48550/arxiv.2105.12074
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of stochastic incorporation on atomic-precision Si:P arrays

Jeffrey A. Ivie,
Quinn Campbell,
Justin C. Koepke
et al.

Abstract: Scanning tunneling microscope lithography can be used to create nanoelectronic devices in which dopant atoms are precisely positioned in a Si lattice within ∼1 nm of a target position. This exquisite precision is promising for realizing various quantum technologies. However, a potentially impactful form of disorder is due to incorporation kinetics, in which the number of P atoms that incorporate into a single lithographic window is manifestly uncertain. We present experimental results indicating that the likel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
(83 reference statements)
1
3
0
Order By: Relevance
“…Given the computationally prohibitive difficulty of modeling the full dissociation to incorporation pathway, for all simulations we count a bridging BH, BCl, or AlCl on the silicon surface as an eventual incorporation, and all other fragments as non-incorporation events. This mirrors a similar treatment for phosphine from Warschkow et al [77], for which Ivie, Campbell, Koepke et al recently demonstrated agreement with incorporation rates inferred from STM scans for phosphine single donor incorporation within three dimer wide windows [63] that were consistent with prior analyses [78]. In all cases, the adsorption energies of these bridging fragments are so low (typically below -2.0 eV) and the re- on the same dimer row(s), however, we assume that these dopants will dimerize and become electrically inactive and do not count these as incorporations within our model.…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…Given the computationally prohibitive difficulty of modeling the full dissociation to incorporation pathway, for all simulations we count a bridging BH, BCl, or AlCl on the silicon surface as an eventual incorporation, and all other fragments as non-incorporation events. This mirrors a similar treatment for phosphine from Warschkow et al [77], for which Ivie, Campbell, Koepke et al recently demonstrated agreement with incorporation rates inferred from STM scans for phosphine single donor incorporation within three dimer wide windows [63] that were consistent with prior analyses [78]. In all cases, the adsorption energies of these bridging fragments are so low (typically below -2.0 eV) and the re- on the same dimer row(s), however, we assume that these dopants will dimerize and become electrically inactive and do not count these as incorporations within our model.…”
Section: Methodssupporting
confidence: 81%
“…In other words, the process of a single acceptor incorporating with atomic-precision must be deterministic, not stochastic, to be realistically scalable. Previous work on phosphine has estimated this singledonor incorporation percentage at ≈ 65% when dosed at room temperature, although corroborating kinetic modeling revealed a potential pathway toward deterministic incorporation by increasing the dosing temperature to ∼ 150 °C [63].…”
Section: Introductionmentioning
confidence: 74%
“…In all previously studied systems an incorporation anneal (typically 350 • C) is required in order for the donor atoms to adopt substitutional lattice sites in the surface 13,20,38 . However, this anneal is highly undesirable as it provides a route for the desorption of the donors from the surface, and presents a major obstacle to the scale up to large-scale quantum technological devices 21,22 . Arsine on germanium solves this problem, since the donor atoms are completely substitutionally incorporated into the surface spontaneously upon adsorption at room temperature, and no incorporation anneal is required.…”
Section: Discussionmentioning
confidence: 99%
“…The probability of successfully incorporating phosphorus into silicon using a hydrogen resist was studied by two independent groups and determined to be P incorp. ∼ 70% 21,22 . Since the probability for successfully fabricating N qubits scales as (P incorp. )…”
mentioning
confidence: 99%